(untitled) (Bangladesh Journal of Medical Science, 2013)
Foreign body in the airway is very rare as compared to the alimentary tract. Food particles constitute among the commonest foreign body. The airway obstruction caused by foreign body dislodgement often present with acute emergency condition. The pathognomonic history includes history of choking and noisy breathing. It is an acute emergency and requires immediate medical attention. However in small number of patients the earliest symptom may be ignored leaving only mild neck discomfort. We report a case of comfortable girl with foreign body airway who finally sought treatment after presented with delayed sign and symptoms of partial airway obstruction. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 231-234 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14979